Augmented Environments for Computer-Assisted Interventions 9th International Workshop, AE-CAI 2014, Held in Conjunction with MICCAI 2014, Boston, MA, USA, September 14, 2014, Proceedings - Linte, Cristian A.; Yaniv, Ziv; Fallavollita, Pascal; Abolmaesumi, Purang; Holmes III, David (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2014)
This book constitutes the refereed proceedings of the 9th International Workshop on Augmented Environments for Computer-Assisted Interventions, held in conjunction with MICCAI 2014, in Boston, MA, USA in September 2014. The 15 revised full papers presented were carefully reviewed and selected from 23 submissions. The scope of the workshop spans the theoretical and practical aspects of augmented reality and visualization computer assisted intervention, interventional imaging, image-guided robotics, image-guided intervention, surgical planning and simulation, systematic extra- and intra-corporeal imaging modalities, general biological and neuroscience image computing, patient specific modeling, and medical image understanding.